Chard (Beta vulgaris L. var. cicla) extract ameliorates hyperglycemia by increasing GLUT2 through Akt2 and antioxidant defense in the liver of rats - ŞENER, GÖKSEL; KABASAKAL, LEVENT (ELSEVIER GMBH, 2014)
Chard is a plant used as an alternative hypoglycemic agent by diabetic people in Turkey. The aim of this study was to examine the molecular mechanism of hypoglycemic effects of chard extract. Male Sprague-Dawley rats (6-7 months old) were divided into five groups for this investigation: (1) control, (2) hyperglycemic, (3) hyperglycemic+chard, (4) hyperglycemic + insulin, (5) hyperglycemic + chard + insulin. Fourteen days after animals were rendered hyperglycemic by intraperitoneal injection of 60 mg/kg streptozotocin, the chard water extract (2 g/kg/day) or/and insulin (6 U/kg/day) was administered for 45 days. Hypoglycemic effect of chard extract was demonstrated by a significant reduction in the fasting blood glucose and increased glycogen levels in liver of chard extract-treated hyperglycemic rats. Moreover, activity of adenosine deaminase, which is suggested as an important enzyme for modulating the bioactivity of insulin, was decreased by chard treatment. Immunostaining analysis showed increased nuclear translocation of Akt2 and synthesis of GLUT2 in the hepatocytes of chard or/and insulin-treated hyperglycemic rats. The oxidative stress was decreased and antioxidant defense was increased by chard extract or/and insulin treatment to hyperglycemic rats according to the decreased malondialdehyde formation, the activities of catalase, superoxide dismutase, myeloperoxidase and increased glutathione levels. These findings suggest that chard extract might improve glucose response by increasing GLUT2 through Akt2 and antioxidant defense in the liver. (C) 2013 Elsevier GmbH. All rights reserved.
Keywords: Akt2; Chard extract; Hyperglycemia; GLUT2; Liver; Oxidative stress; INSULIN-RESISTANCE; LIPID-PEROXIDATION; POTENTIAL ROLE; KINASE; STREPTOZOTOCIN; DNA; ACTIVATION; TOXICITY; VESICLES; GLYCOGEN